2022
DOI: 10.1037/cou0000596
|View full text |Cite
|
Sign up to set email alerts
|

How young psychotherapists experience working with older patients.

Abstract: Preliminarily findings from experimental and survey research suggests that psychotherapy with older adults is an area of practice in which psychotherapists do not feel positive and confident. This qualitative study is the first to explore how young psychotherapists experience and perceive their therapeutic work with older patients. To do so, we provide an in-depth perspective of how young (aged 27-35) psychotherapists experience providing psychotherapeutic treatment for older patients (aged over 65). Semistruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
14
1
1
Order By: Relevance
“…We identified three specific areas of tension: (a) pushing for change versus acknowledging limitations , (b) providing help versus maintaining boundaries , and (c) behaving as a guest versus host of a psychotherapy session. These three dilemmas add to the limited body of evidence on psychotherapists’ clinical and ethical experiences of conducting psychotherapy with older adults (Boschann et al, 2022; Jones & Knowles, 2021; Lederman & Shefler, 2022, 2023) and outreach treatment with (older) adults in particular (Knapp & Slattery, 2004; Maxfield & Segal, 2008; Yang et al, 2009). In line with previous research, our analysis identified maintaining professional boundaries as a central challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified three specific areas of tension: (a) pushing for change versus acknowledging limitations , (b) providing help versus maintaining boundaries , and (c) behaving as a guest versus host of a psychotherapy session. These three dilemmas add to the limited body of evidence on psychotherapists’ clinical and ethical experiences of conducting psychotherapy with older adults (Boschann et al, 2022; Jones & Knowles, 2021; Lederman & Shefler, 2022, 2023) and outreach treatment with (older) adults in particular (Knapp & Slattery, 2004; Maxfield & Segal, 2008; Yang et al, 2009). In line with previous research, our analysis identified maintaining professional boundaries as a central challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We considered professional experience as a selection characteristic based on Rønnestad et al (2016), who demonstrated the relevance of psychotherapists’ professional experience for their role perception (experienced psychotherapists achieve a deeper integration of their personal and professional qualities than their colleagues with less experience). We considered age and professional activity as selection characteristics based on Boschann et al (2022), who found that psychotherapists’ age and the treatment setting impacted their self-perceptions of treating older patients. We thus selected the sample to include psychotherapists who differed with regard to age, level of professional experience, and psychotherapists who worked in both inpatient and outpatient settings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Education and training in the care of older adults is important to enhance a sense of competence as well as to address negative attitudes (Levy & Macdonald, 2016;Lytle & Levy, 2019) and foster interest (Merz et al, 2017). Though there are unique challenges to working with older adult clients, particularly amongst young psychotherapists, supportive training and supervision may help to facilitate increased competence and comfort working with this population (Boschann et al, 2022). Educational interventions are often geared toward improving attitudes toward older adults, with positive clinical interactions seemingly the most influential (see systematic reviews by Chonody, 2015;Ross et al, 2018).…”
Section: Introductionmentioning
confidence: 99%